Immediate and short-term effects of pile-driving on Hector’s dolphin in Lyttelton Harbour, Aotearoa New Zealand - Clement, Deanna M.; Pavanato, Heloise; Lenky, Crystal; Pine, Matthew K. (Frontiers in Marine Science, 2025)
Ports in Aotearoa New Zealand have or are currently undergoing extensive infrastructure developments to accommodate the global trend in larger commercial vessels and cruise ships. With no national standards for underwater noise, Lyttelton Port Company is the first Aotearoa New Zealand port to undertake monitoring to assess pile-driving generated noise effects on local Hector’s dolphins, an endemic and nationally vulnerable species. The immediate and shorter-term responses of this species were monitored with autonomous underwater recorders and assessed to understand how dolphins reacted to pile-driving activities. General and site-specific model results indicated that as sound exposure levels from impact pile-driving increased, declines in dolphin detections varied spatially with immediate declines occurring at sites less than 1km for the source. Declines in detections were still apparent up to 2km, but more evident with greater noise exposure levels and in warmer water conditions. Once piling ceased for a day, Hector’s dolphins moved back into inner harbor waters within hours, and acoustic detections returned to within pre-piling levels gradually over a few days. While there is no evidence that dolphins abandoned the port region over the construction period, our findings established a longer-term decline in dolphin detections coinciding with the 2019 construction period that had not returned to pre-construction levels by May 2020. Despite evidence that mitigation measures were successful at protecting against auditory injury impacts, additional measures are warranted for future port infrastructure developments to avoid short and longer term impacts on Hector’s dolphin use of the harbor and while Aotearoa New Zealand develops or adopts national underwater noise guidelines.